2006
DOI: 10.1542/peds.2005-2429
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions Among Children Over a 10-Year Period

Abstract: Measures to improve detection and reporting of adverse drug reactions by all health care professionals should be undertaken, to enhance our understanding of the nature and impact of these reactions in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
99
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 32 publications
8
99
2
1
Order By: Relevance
“…8 It has been observed that ADR in pediatric not only result in hospital admissions or prolonged hospitalization but also may lead to permanent disability or even death. 9 Kanish R conducted a study on prescribing pattern of antibiotics in the department of paediatrics in a tertiary care medical college hospital. Cephalosporins were maximally prescribed followed by aminoglycosides which is also the trend seen in another study done by Pandey AA on prescription analysis of paediatric outpatient practice in Nagpur city.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been observed that ADR in pediatric not only result in hospital admissions or prolonged hospitalization but also may lead to permanent disability or even death. 9 Kanish R conducted a study on prescribing pattern of antibiotics in the department of paediatrics in a tertiary care medical college hospital. Cephalosporins were maximally prescribed followed by aminoglycosides which is also the trend seen in another study done by Pandey AA on prescription analysis of paediatric outpatient practice in Nagpur city.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs most frequently associated with adverse reactions are antibiotics, antipyretics and non -steroidal anti-inflammatory. [5][6][7] Hence, the present study was undertaken to evaluate the clinical spectrum of all paediatric ADRs in patients admitted to a paediatric unit of tertiary care teaching hospital. It also emphasises on the need and importance of an effective pharmacovigilance programme.…”
mentioning
confidence: 99%
“…La baja tasa de notificaciones de sospechas de RAM 29,30 refleja un sistema de notificación aún incipiente, que puede mejorar mediante actividades de motivación y capacitación del equipo de salud. Una revisión sistemática de 102 estudios prospec-tivos 9 de RAM en niños, encontró gran variación cuando se compararon las tasas de incidencia reportadas desde estudios observacionales; entre los estudios, 36 estimaron una tasa de incidencia para RAM durante la hospitalización desde 0,6% a 16,8% de los pacientes; considerando que una de las principales dificultades, cuando se comparan tasas de incidencia para RAM, es que los estudios difieren en la calidad metodológica, escenario clínico, características de la población y duración del estudio.…”
Section: Discussionunclassified